(untitled) (Journal of Parents and Teachers, 2026)
Artificial intelligence is already present in classrooms, yet teachers have not received the training needed to deal with this situation. It is urgent that teachers receive training focused on five key areas: conceptual understanding, the primacy of teaching, critical and reflective use, ethics and privacy, and continuous professional development. The aim is not merely to teach how to use tools, but to restore the teacher’s role as an intellectual and ethical guide in the age of AI.